Effect of Ageing Process and Brushing on Color Stability and Surface Roughness of Treated White Spot Lesions: An in vitro Analysis - Almulhim K; Khan AS; Alabdulghani H; Albasarah S; Al-Dulaijan Y; al-Qarni FD (Dove Medical Press, 2021)
Khalid Almulhim,1 Abdul Samad Khan,1 Hanan Alabdulghani,2 Sara Albasarah,2 Yousif Al-Dulaijan,3 Faisal D al-Qarni3 1Department of Restorative Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 3Department of Substitutive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Faisal D al-QarniDepartment of Substitutive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaTel +966 13 333 1404Email fdalqarni@iau.edu.saPurpose: To evaluate the effect of ageing process and brushing on the color stability and surface roughness of white spot lesions treated with resin infiltration or remineralization.Patients and Methods: Artificial white spot lesions were created on the facial surface of extracted bovine teeth. Specimens were divided into three main groups based on treatment received: resin infiltration (Icon), MI Paste Plus (MI) or no treatment (control). Specimens underwent pH cycling for 7 days, followed by brushing with toothbrush simulator. Specimens were then immersed in three different solutions (water, cranberry juice, or coffee) for 7 days. Surface roughness (SR) and color stability (CS) assessments were performed at baseline and after each test. One-way and two-way ANOVA were used to calculate the statistical comparisons between the groups and significance considered at P < 0.05.Results: Icon group had the least color change after pH cycling, while MI showed the least color change after brushing test. Immersion in coffee produced the highest color change in all groups, followed by cranberry juice. Icon group had the best color stability when immersed in cranberry juice or coffee. Control and the MI treated specimens showed gradual increase of SR after pH cycling and brushing test, while Icon group had improved surface properties. Brushing test alone produced less color change in comparison with immersion in cranberry juice and coffee; however, brushing increased SR.Conclusion: Icon treatment showed superior color stability and surface roughness, compared to the control and the MI treated teeth. Brushing had less influence on color change compared to the immersion in cranberry juice or coffee.Keywords: white spot lesion, surface roughness, color stability, resin infiltration